THE EFFECT OF HEALTH EDUCATION USING ANIMATED VIDEO ON KNOWLEDGE OF DIABETES MELLITUS PREVENTION IN SCHOOL-AGE CHILDREN - Tia Afrilita Badaria; Nurdiana Djamaluddin; Maryadi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Diabetes mellitus (DM) among school-age children demonstrates a concerning upward trend in Indonesia. The limited understanding of adolescents regarding DM prevention necessitates effective educational strategies tailored to their developmental characteristics. Purpose: This study aims to evaluate the effectiveness of animated video–based education on school students’ knowledge of diabetes mellitus. Methods: A quasi-experimental design with a pretest–posttest control group approach was employed at SMPN 10, Gorontalo City. A total of 58 students were recruited through purposive sampling (intervention group n=29; control group n=29). The intervention group received health education via an animated video, while the control group received only a conventional lecture. Knowledge was assessed using a validated 10-item multiple-choice questionnaire. Data were analyzed using the paired sample t-test, the wilcoxon signed-rank test, and the independent sample t-test. Results: A statistically significant difference in knowledge gain was observed between the intervention group (33.45±9.24) and the control group (4.21±2.64) (p=0.000). Conclusion: Health education delivered via animated video was more effective than conventional lectures in improving knowledge of DM prevention among school-age adolescents.